Ethical Principles Of Preschool Teachers - Yeni, Melia Distri; Olivia, Sintia; Apriyani, Desi; Nurwita , Syisva (Jurnal Pendidikan Rafflesia, 2025)
The ethics of Early Childhood Education (PAUD) teachers served as an essential foundation in shaping the character, professionalism, and quality of children’s education. PAUD teachers were not only responsible for teaching but also acted as role models in behavior, communication, and the daily application of moral values. This study aimed to examine the ethical principles of PAUD teachers, including moral responsibility, honesty, fairness, exemplary conduct, and professional relationships with students, parents, and the community. The method employed was qualitative descriptive with a literature review approach from various relevant scholarly sources. The results indicated that the implementation of professional ethics by PAUD teachers contributed to creating a safe, conducive, inclusive learning environment grounded in strong moral values. The application of teacher ethics also played a role in enhancing parental trust, the quality of children’s social interactions, and the effectiveness of the learning process. Therefore, strengthening professional ethics became a strategic measure to improve the quality of early childhood education in Indonesia while shaping PAUD teachers who were characterized, professional, and responsible.